Determining The Relationship Between Speed and Branch Specific Test for Fencers in The U 10-12 Categories - Sercin Kosova; Merve Koca Kosova; Celal Gençoğlu; Hikmet Gümüş; Fırat Özdalyan; Egemen Mancı (Selcuk University, 2021)
Success in fencing is gained by making quick decisions and acting quickly during the bout. This study aimed to determine the body composition of fencers competing in the U 10-12 age categories and to examine the relationship between the 30-m speed test (30-m ST) and the 7-m repeat lunge ability test (7-m RLAT). Thirty-eight sabre fencers (female: 25 and male: 13) participated in the study. The anthropometric properties of the participants were determined, then the 30-m ST and the 7-m RLAT, a specific test for fencing, were performed. The differences between sexes were evaluated using the Mann-Whitney U test because the data were not distributed normally, and Spearman correlation analysis was performed to determine the relationship between performance tests. When the results of the study were examined, there was no significant difference between the sexes in the physical characteristics and performance tests of the athletes (p gt;0.05). Also, when all fencers were evaluated together, a significant relationship was found between the 30-m ST and the 7-m RLAT (rs(36)=0.526, p=0.001). When the sexes were examined separately, a significant relationship was found between the 30-m ST and the 7-m RLAT only in the male group (rs(23)=0.659, p lt;0.001). The 7-m RLAT can be used instead of or in addition to anaerobic power and speed tests for performance measurement in fencers.